Regulation of the integrin αVβ3- actin filaments axis in early osteogenic differentiation of human mesenchymal stem cells under cyclic tensile stress - Yan Peng; Rongmei Qu; Yuchao Yang; Tingyu Fan; Bing Sun; Asmat Ullah Khan; Shutong Wu; Wenqing Liu; Jinhui Zhu; Junxin Chen; Xiaoqing Li; Jingxing Dai; et al. (Cell Communication and Signaling, 2023)
Abstract Background Integrins are closely related to mechanical conduction and play a crucial role in the osteogenesis of human mesenchymal stem cells. Here we wondered whether tensile stress could influence cell differentiation through integrin αVβ3. Methods We inhibited the function of integrin αVβ3 of human mesenchymal stem cells by treating with c(RGDyk). Using cytochalasin D and verteporfin to inhibit polymerization of microfilament and function of nuclear Yes-associated protein (YAP), respectively. For each application, mesenchymal stem cells were loaded by cyclic tensile stress of 10% at 0.5 Hz for 2 h daily. Mesenchymal stem cells were harvested on day 7 post-treatment. Western blotting and quantitative RT-PCR were used to detect the expression of alkaline phosphatase (ALP), RUNX2, β-actin, integrin αVβ3, talin-1, vinculin, FAK, and nuclear YAP. Immunofluorescence staining detected vinculin, actin filaments, and YAP nuclear localization. Results Cyclic tensile stress could increase the expression of ALP and RUNX2. Inhibition of integrin αVβ3 activation led to rearrangement of actin filaments and downregulated the expression of ALP, RUNX2 and promoted YAP nuclear localization. When microfilament polymerization was inhibited, ALP, RUNX2, and nuclear YAP nuclear localization decreased. Inhibition of YAP nuclear localization could reduce the expression of ALP and RUNX2. Conclusions Cyclic tensile stress promotes early osteogenesis of human mesenchymal stem cells via the integrin αVβ3-actin filaments axis. YAP nuclear localization participates in this process of human mesenchymal stem cells. Video Abstract